Effects of Different Drying Methods on Physicochemical Properties, Antioxidant Activity and Flavor Profile of Lentinus edodes Powder - SHENG Menglong, LIN Songyi, MA Tingting, ZHANG Tong, LI Yulu, CHEN Dong (Shipin Kexue)
This research investigated the impacts of various drying methods, including hot-air drying, hot-air-microwave drying, heat-pump drying, vacuum-freeze drying, microwave-vacuum drying, and multi-stage hot-air drying, on the physicochemical properties, antioxidant capacity and flavor profile of Lentinus edodes powder (LEP). The results demonstrated that vacuum-freeze-dried LEP was superior to LEP produced using the other drying methods in terms of physicochemical properties such as water absorption index, expansion ratio, and color. Moreover, vacuum-freeze-dried LEP had the highest total phenolic content (1.345 mg/g) and strongest antioxidant capacity in terms of 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical and 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) cation radical scavenging capacity. In contrast, microwave-dried LEP showed the lowest antioxidant capacity. Analysis by electronic nose and gas chromatography-ion mobility spectrometry (GC-IMS) revealed that the major volatile compounds in the six LEPs included sulfur-containing compounds, aldehydes, alcohols, ketones, and esters, and there were significant differences in the aroma profiles of these LEPs. Notably, heat-pump-dried LEP exhibited the highest levels of alcohols and esters. Hot-air-dried LEP exhibited the highest levels of aldehydes. Vacuum-freeze drying was conducive to retaining aroma compounds. The results of electronic tongue analysis indicated that hot-air-microwave dried LEP had high umami and low bitterness. These findings could provide a theoretical foundation for the development and application of LEP as a food ingredient.